Evolving Anatomy Education: Bridging Dissection, Traditional Methods, and Technological Innovation for Clinical Excellence - Luis Alfonso Arráez-Aybar (Anatomia, 2025)
Anatomy education has long served as a cornerstone of medical training, equipping healthcare professionals with the foundational knowledge necessary for clinical practice. However, the discipline has undergone significant transformations in response to evolving curricula, ethical considerations, and technological advancements. This paper explores the historical development, current state, and future trajectory of anatomy education, focusing on challenges such as ethical concerns regarding cadaveric dissection, and the need for cost-effective alternatives. The study examines innovative teaching methods, including virtual reality, augmented reality and artificial intelligence, which enhance anatomical learning by providing interactive, scalable educational experiences. Additionally, it discusses the integration of anatomy with clinical practice through imaging technologies, competency-based education, and evidence-based approaches. While modern innovations offer valuable learning tools, they cannot entirely replace the hands-on experience and professional identity formation fostered by cadaveric dissection. A balanced approach that combines traditional methodologies with digital advancements is essential for optimizing anatomy education. By leveraging both physical and virtual resources, educators can enhance anatomical comprehension, improve clinical preparedness, and ensure that future healthcare professionals develop both technical expertise and ethical awareness. This paper underscores the need for continued adaptation in anatomy education to align with the demands of modern medicine while preserving its core educational values.